Implementing CO2-based controlled atmosphere treatments in big bags with inexpensive liners - Bartosik, Ricardo Enrique (2024)
The production of specialty grains such as quinoa, amaranth, teff, popcorn, peanuts, and different organic crops involves meeting specific safety requirements, including the necessity to be free of insecticide residues. Consequently, in recent years there has been a growing interest in alternative controlled atmosphere (CA) treatments. On the other hand, market opportunities have required the adaptation of CA application to big bags and raffia containers typically holding 1 m3 of product. Normally, the CA treatment system consists of a gas application system (CO2 or N2), an internal polyethylene bag with specific design and gas barrier properties, and a closure via heat sealing. However, these systems can prove costly, limiting their usability for numerous products. The purpose of this experiment was to assess the feasibility of implementing a CA treatment (with CO2) through the design of simpler and more cost-effective technologies, aiming to expand the user base of CA treatments. The experiment involved analyzing the effectiveness of a simple and economical polyethylene bag (70 microns, without a gas barrier) in combination with two closure systems: a simple one (twisting-folding-knot) versus the control system (heat-sealing). The control condition was established when a concentration × time product (Ct product) of 12,000 %h was reached (minimum allowed concentration of 40%). The initial injection created an internal atmosphere of 90% CO2. Overall, it was observed that treatments with a heat-sealed closure achieved satisfactory control conditions with a single initial injection, reaching the target Ct product while consistently maintaining the CO2 concentration above 40%. In contrast, treatments with the knot-closure method did not ensure adequate sealing, requiring gas reinjections in some cases to achieve the control condition. In conclusion, this study demonstrates the feasibility of implementing a successful CA treatment in raffia big bags using low-cost polyethylene liners. However, it is crucial to employ the heat-sealed closure system to ensure the efficacy of the treatment.